An Evaluation of Traits, Nutritional, and Medicinal Component Quality of Polygonatum cyrtonema Hua and P. sibiricum Red. - Hu, Yan; Yin, Minzhen; Bai, Yunjun; Chu, Shanshan; Zhang, Ling; Yang, Mei; Zheng, Xiaowen; Yang, Zhengyang; Liu, Junling; Li, Lei; Huang, Luqi; Peng, Huasheng (Frontiers in Plant Science, 2022)
Polygonati rhizoma (Huangjing in Chinese) is a traditional and classic dual-purpose material used in food and medicine. Herbalists in China and Japan have noticed several different rhizome types in Huangjing with different qualities. Rhizome of Polygonatum cyrtonema Hua and P. sibiricum Red. are divided into five types: “Jitou-type” Polygonati rhizoma (JTPR), atypical “Jitou-type” Polygonati rhizoma (AJTPR), “Jiang-type” Polygonati rhizoma (JPR), “Cylinder-type” Polygonati rhizoma (CPR), and “Baiji-type” Polygonati rhizoma (BJPR). This study observed the microstructure and histochemical localization of polysaccharides, saponins, and proteins in the rhizomes of Huangjing. Nutritional and medicinal component data and antioxidant capacity (DPPH and ABTS) were analyzed to evaluate the quality of different types of Huangjing. The results showed that the comprehensive quality of the rhizomes, BJPR and JTPR, was better, regardless of their nutritional or medicinal values. Altogether, these results could recommend future breeding efforts to produce Huangjing with improved nutritional and medicinal qualities.